Unsung Heroes of Mission Bible Translation in Colonial West Africa: Ludwig Adzaklo of the Bremen Mission in German Togoland - Michael F. Wandusim (Religions, 2024)
The Africanisation of Christianity in Africa is closely linked to the availability of the Bible in African mother tongues. However, mission-led Bible translation in Africa in the nineteenth and early twentieth centuries was not solely the work of European missionary linguists. Africans, such as Ludwig Adzaklo of the Bremen Mission, played essential roles in this process. Nevertheless, African translators like him were considered as mere Sprachgehilfe (language assistants) to the missionaries and not as co-translators. After a postcolonial analysis of archival data on the translation of the Old Testament into Ewe by Ludwig Adzaklo and Jakob Spieth, this study argues that Adzaklo was not just Spieth’s Sprachgehilfe but a co-translator on the project. Being referred to as Spieth’s Sprachgehilfe was a colonial-missionary label that denied Adzaklo’s agency in mission-led Bible translation in Africa. Therefore, the study suggests that Adzaklo should be viewed as an early Ewe mother-tongue Bible translator in the history of West African Christianity.